PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL EXPERIENTIAL LEARNING DENGAN PENDEKATAN KONSTRUKTIVISME DI SMA NEGERI 2 TONDANO - Heldi Angelia Gavrilla Ngkunda; Tineke Makahinda; Djeli Alvi Tulandi (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This study aims to develop leatning tools based on experiential learning models with constructivistapproach so as to produce valid, practical and effective learning tools that can improve learningprocesses and outcomes in the material of momentum and impulse in class X B students of SMA Negeri2 Tondano. The learning tools produced are teaching modules, teaching materials and StudentWorksheets. The type of research used in this research is development research with the 4D researchmodel, namely define, design, development and disseminate. The results of this study are: (1) theresulting device is